Improved Design and Application of Vertical Axis Wind Turbine Gearbox - Zhu Zhiyuan (Jixie chuandong)
The vertical planetary gear box which is applied to the vertical axis wind turbine is introduced.By means of the improved design of the load balancing,lubrication and sealing of the gearbox,the reliability of the gearbox is greatly improved.